Practice patterns of post-radical prostatectomy incontinence surgery in Ontario - Wallis, Christopher; Herschorn, Sender; Liu, Ying; Carr, Lesley; Kodama, Ronald T; Klotz, Laurence; Saskin, Refik; Nam, Robert K (Canadian Urological Association Journal, 2014)
Introduction: We assess the practice patterns of artificial urinary sphincter (AUS) and urethral sling insertion after radical prostatectomy (RP) from a large population-based cohort. Methods: We examined 25 346 men in Ontario, Canada who underwent RP between 1993 and 2006. Using hospital and cancer registry data, we identified patients who subsequently underwent an incontinence procedure. We characterized the practice patterns of post-prostatectomy incontinence procedures across Ontario during the study interval. Results: A total of 703 (2.8%) men underwent subsequent insertion of an AUS and 282 (1.1%) underwent a urethral sling procedure (985 total incontinence procedures, 3.9%) over the study period. During the study period, 121 hospitals performed RP. Among them, 32 (26%) hospitals performed both RP and AUS/sling procedures, and 89 (74%) performed RP only. Four hospitals performed AUS/sling procedures but not RP. Of the 36 institutions that performed AUS/sling procedures, the median annual case volume was 0.29 (interquartile range: 0.083-0.75). Of all incontinence procedures, 56% were performed at 3 academic institutions. When examining observed rates of AUS/sling procedures compared with expected rates from the overall cohort, 15 of 32 hospitals (47%) performed significantly fewer incontinence procedures than expected given their RP case volume (p range: <0.0001–0.0390) and 5 (16%) performed significantly more (p range: <0.0001–0.038). Conclusions: A small number of academic institutions provide most of the surgical care for men with incontinence following RP in Ontario. Many centres that perform RP refer out to other centres to surgically manage their patients’ incontinence.